Structure–Activity Relationship Analysis of Flavonoids and Its Inhibitory Activity Against BACE1 Enzyme Toward a Better Therapy for Alzheimer’s Disease - Mohamed Yusof, Nur Intan Saidaah; Abdullah, Zafirah Liyana; Othman, Norodiyah; Mohd Fauzi, Fazlin (Frontiers in Chemistry, 2022)
Drug development in Alzheimer’s Disease (AD) suffers from a high attrition rate. In 2021, 117 agents tested in Phases I and II and 36 agents tested in Phase III were discontinued. Natural product compounds may be good lead compounds for AD as they contain functional groups that are important for binding against key AD targets such as -secretase enzyme (BACE1). Hence, in this study, 64 flavonoids collected from rigorous literature search and screening that have been tested from 2010 to 2022 against BACE1, which interferes in the formation of amyloid plaque were analysed. The 64 unique flavonoids can be further classified into 5 core fragments. The flavonoids were subjected to clustering analysis based on its structure, and each representative of the clusters were subjected to molecular docking. There were 12 clusters formed where only 1 cluster contained compounds from 2 different core fragments. Several observations can be made where (i) flavanones with sugar moieties showed higher inhibitory activity compared to flavanones without sugar moieties. The number of sugar moieties and position of glycosidic linkage may also affect the inhibitory activity. (ii) Non-piperazine substituted chalcones when substituted with functional groups with decreasing electronegativity at the para position of both rings result in a decrease in inhibitory activity. Molecular docking indicates that ring A is involved in hydrogen bond whereas ring B is involved in van der Waals interaction with BACE1. (iii) Hydrogen bond is an important interaction with the catalytic sites of BACE1, which are Asp32 and Asp228. As flavanoids contain favourable structures and properties, this makes them an interesting lead compound for BACE1. However, to date, no flavonoids have made it through clinical trials. Hence, these findings may aid in the design of highly potent and specific BACE1 inhibitors, which could delay the progression of AD.